Crisis in Psychiatric Diagnosis? Epistemological Humility in the DSM Era. Issue 6 (30th November 2020) - Kinghorn, Warren
Abstract: The modern editions of the Diagnostic and Statistical Manual of Mental Disorders (DSM), beginning with DSM-III in 1980, emerged in response to notable challenges to psychiatry's practices and ways of knowing in the early 1970s. Because these challenges threatened psychiatry's scientific self-understanding and moral authority, they exemplify what Alasdair MacIntyre has termed "epistemological crisis." As a response to crisis, the modern DSM has been a stunning political achievement, providing the central diagnostic constructs around which psychiatric research, practice, and reimbursement has been organized for four decades. Indeed, the DSM's authority survives in the face of ongoing trenchant scientific and philosophical critique. But if psychiatry is to be healthy, it must be epistemologically humble, reckoning honestly with the limits of the DSM before a future epistemological crisis destabilizes it entirely.